Letter from R.E. Preston to Margaret M. Booth, February 2, 1888 - Preston, Robert E., 1836–1911 (1888)
Letter from Robert E. Preston (1836-1911), of the United States Mint Bureau, to Margaret M. Booth née Cardeza concerning Preston's attempts to secure relief for James Booth from responsibility for making good on two stolen bars of silver from the United States Mint.
Keywords: Booth, James Curtis, 1810-1888; Bills, Legislative; Martinez Cardeza, Margaret; Preston, Robert E., 1836–1911; United States Mint; Mint of the United States